Model Edukasi Keamanan Digital Anak Berbasis Evaluasi Terstruktur pada Program KKN Internasional di Malaysia - Eclesianetha Ayu Pasha; Yudo Bismo Utomo; Erlin Widya Fatmawati (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The increasing use of digital technology among children has not been fully matched by adequate digital security awareness, potentially exposing them to risks such as misuse of personal data, cyberbullying, and negative online content. This community service program aimed to implement a child digital security education model based on structured evaluation and to examine its effectiveness within the International Community Service Program in Malaysia as a systematic and measurable preventive intervention. The activity involved 25 students from a non-formal educational institution. The model was implemented through interactive learning that included awareness building, digital risk identification, prevention strategy training, and structured evaluation using pre-test and post-test instruments. The results showed an increase in the average score from 55% to 85%, with a 30% improvement and an N-Gain value of 0.67 (moderate category). A total of 88% of participants experienced an increase in individual scores and exceeded the minimum target of 60%. These findings indicate that a structured evaluation approach is effective in improving children's understanding of digital security and can be applied sustainably in non-formal educational settings.